Analisis Uji Multikolinearitas Variabel Lingkungan Hutan Bakongan-Bengkung, Kawasan Ekosistem Leuser: Implikasi Terhadap Habitat Spesies Kunci - Ananda, Ilham; Dahlan, Dahlan; Dharma, Wira (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to analyze the multicollinearity of environmental variables in the Bakongan-Bengkung Forest, part of the Leuser Ecosystem, to understand its implications for the habitat of key species such as Sumatran elephants, Sumatran rhinoceros, Sumatran tigers, and Sumatran orangutans. The research was conducted in August 2023 across an area of 75.912,46 hectares spanning three districts in Aceh. The data utilized includes elevation, slope, river density estimation, Normalized Difference Vegetation Index (NDVI), distance from roads, and annual rainfall, sourced from various geospatial datasets. Data processing was performed using ArcGIS 10.3, Google Earth Engine (GEE), and RStudio 4.2.2. Multicollinearity testing was carried out using Pearson correlation coefficients to identify relationships between environmental variables. The analysis revealed a significant positive correlation between elevation and annual rainfall, with a correlation coefficient of 0,724, indicating a strong linear relationship. This correlation suggests that higher elevations in the area are associated with increased rainfall, likely due to orographic effects. These findings are crucial for conservation planning and habitat management for wildlife. The correlation between elevation and annual rainfall should be considered when developing accurate habitat models for key species in the Bakongan-Bengkung Forest, to ensure effective and sustainable conservation strategies.